1992
DOI: 10.1002/lsm.1900120206
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations of Holmium:YAG laser tissue interaction using human uterus

Abstract: Preliminary observations of a pulsed Ho:YAG laser on human uterine tissue in-vitro are presented. The tissue effect on the uterine myometrium was demonstrated using fresh uteri which had been subjected to laser energy. The laser crater and surrounding zone of thermal necrosis (ZTN) was quantified. Measurements demonstrated a consistent narrow ZTN (0.8-1.8 mm) irrespective of power or pulse frequency used. The percentage forward transmission of laser energy through 1 mm of myometrium was investigated using a py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Haase, et al 87 found a comparable zone of necrosis extending 100 to 1000 μm beyond the crater edge when this laser was used to ablate atherosclerotic plaques in arterial specimens. A somewhat larger zone of necrosis extending 800 to 1800 μm beyond the crater edge was noted by Duffy, et al 99 when the holmium:YAG laser was used to ablate tissue of the human uterus.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Haase, et al 87 found a comparable zone of necrosis extending 100 to 1000 μm beyond the crater edge when this laser was used to ablate atherosclerotic plaques in arterial specimens. A somewhat larger zone of necrosis extending 800 to 1800 μm beyond the crater edge was noted by Duffy, et al 99 when the holmium:YAG laser was used to ablate tissue of the human uterus.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have demonstrated the ability of this laser to break apart gallstones 96,97 and to remove deposits from heart valves 98 . Experiments have also been conducted to determine the efficacy of the holmium:YAG laser in gynecologic, 99 gastrointestinal, 100‐103 vascular, 104 and dental 105 surgical procedures.…”
Section: Use Of Lasers For Rhinologic Surgerymentioning
confidence: 99%
“…In addition, high-speed photographs of the ablation process have revealed that explosive removal of tissue occurs [25,26]. Tissue interaction studies on nonskeletal tissues using laser systems operating in the midinfrared have shown that the extent of thermal tissue damage varies according to the type of tissue [11,18] and increases with higher repetition rates.…”
Section: Discussionmentioning
confidence: 98%
“…Previous experimental studies on test cuts in different tissues in vitro and in vivo have shown that 2,940 nm and 2,120 nm radiation can effectively cut a variety of tissues, especially bone, leaving between 5 and 600 m of damage [8][9][10][11]. The presence of plasma illumination during hardand soft-tissue processing with high fluences suggests that thermal ionization or photoablation occurs.…”
Section: Introductionmentioning
confidence: 96%
“…This property of the Ho:YAG laser has proven to be useful in other specialties in addition to thoracic surgery, such as urology [10,11], orthopedics [12,13], general gastroenterological surgery [14,15], otorhinology [16], and gynecology [17]. In the future, more noninvasive surgery will be possible with the Ho:YAG laser in conjunction with the development of various new biocompatible repair materials.…”
Section: Discussionmentioning
confidence: 99%